The Heralds at the Bells: Messages of Hope from West Balkan Bards During the Coronavirus Pandemic - Jurić , Dorian (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2021)
Between March and May of 2020, a number of guslars (bards) and other traditional singers from Bosnia-Herzegovina, Croatia, Montenegro, and Serbia flooded YouTube with songs about the COVID-19 pandemic. Though the musicians chose divergent vantage points from which to approach the topic of the pandemic, all settled on a similar goal. They sought to deliver a message of solidarity and hope to those struggling with the realities of life under lockdown measures and to allay the fears and uncertainties that spread with the virus. This article provides a critical overview of the guslars’ songs to explore their shared and divergent tropes, themes, and tones, and to highlight the goals of their singers in disseminating their messages in traditional form. Here I comment on what the high degree of convergence in the songs’ final messages reveals about vernacular responses to the pandemic and folk views on the measures taken to halt the virus’s spread. Finally, the article places these songs into a wider historical context of contemporary singing to the gusle, remarking on the vagaries of navigating authority when one sings subjective opinion in the name of a collective.